2005
DOI: 10.1002/adem.200400214
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Predictions for the Intrinsic Converse Longitudinal Piezoelectric Constants of Lead Zirconate Titanate Epitaxial Films

Abstract: The orientation dependences of the converse longitudinal piezoelectric coefficient d33,f are calculated for epitaxial Pb(ZrxTi1–x)O3 films with different compositions. This calculation showed that the substrate clamping plays an important role on determining the piezoelectric properties of ferroelectric thin films, and thus may serve as an example illustrating why physical properties of thin films are different from bulk materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…[24,25] It was found that a (001) oriented film has the largest intrinsic d 33 for both tetragonal and rhombohedral compositions, similar to the results calculated for the bulk materials. [26,27] The with the calculations based on the assumption that the 90°do-main walls are mobile.…”
Section: Discussionsupporting
confidence: 82%
“…[24,25] It was found that a (001) oriented film has the largest intrinsic d 33 for both tetragonal and rhombohedral compositions, similar to the results calculated for the bulk materials. [26,27] The with the calculations based on the assumption that the 90°do-main walls are mobile.…”
Section: Discussionsupporting
confidence: 82%
“…Common applications of PTFs are composed of surface acoustic wave devices [6,7], non-volatile random access memory devices [8,9], infrared sensors [10,11], optical waveguide modulators [12,13], and nanogenerators for energy harvesting [14,15]. In addition, most PTFs are complex ceramic thin films exhibiting complex stoichiometry, co-existence of multiple phases, and various domain morphology, which greatly contribute to functional properties, such as piezoelectricity, dielectricity, and ferroelectricity [16,17]. Therefore, PTFs have drawn great attention from both electronic engineering and materials engineering communities.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving epitaxial growth with (100) orientation is known to maximize the piezoelectric response compared to the polycrystalline films [18][19] . However the piezoelectric response is still drastically reduced compared to intrinsic piezoelectric response due to clamping of the thin film by the substrate [27][28][29] . On application of an electric field in the direction normal to the PZT film surface (longitudinal direction), the longitudinal expansion of the PZT film is coupled to a contraction in the direction parallel to its surface (transverse direction).…”
Section: Introductionmentioning
confidence: 99%